2023
DOI: 10.1038/s41612-023-00385-4
|View full text |Cite
|
Sign up to set email alerts
|

Marked impacts of transient conditions on potential secondary organic aerosol production during rapid oxidation of gasoline exhausts

Abstract: Vehicle emission is a major source of atmospheric secondary organic aerosols (SOA). Driving condition is a critical influencing factor for vehicular SOA production, but few studies have revealed the dependence on rapid-changing real-world driving conditions. Here, a fast-response oxidation flow reactor system is developed and deployed to quantify the SOA formation potential under transient driving conditions. Results show that the SOA production factor varies by orders of magnitude, e.g., 20–1500 mg kg-fuel−1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 61 publications
(101 reference statements)
2
8
0
Order By: Relevance
“…This significantly affected the gas-particle partitioning and reduced the loss of aged low-volatile organic compounds. 15 Considering the neutral property, NaCl material was used as the seed aerosol, generated by an aerosol atomizer (model 3076, TSI Inc.).…”
Section: Tunnel Measurement Setupmentioning
confidence: 99%
See 4 more Smart Citations
“…This significantly affected the gas-particle partitioning and reduced the loss of aged low-volatile organic compounds. 15 Considering the neutral property, NaCl material was used as the seed aerosol, generated by an aerosol atomizer (model 3076, TSI Inc.).…”
Section: Tunnel Measurement Setupmentioning
confidence: 99%
“…A detailed description of the methods can be found in our previous study. 15 The SOA production factors within the bin of 30−40 km/h were extracted to compare with tunnel experimental results. The schematic of the enclosure study combined with tunnel and laboratory experiments is shown in Figure S3.…”
Section: Ofr Simulation Of Tailpipe Exhaustmentioning
confidence: 99%
See 3 more Smart Citations